Analisis Faktor-Faktor Yang Mempengaruhi Stock Return - Sumarna, Alfonsa Dian (UP2M SEKOLAH TINGGI ILMU EKONOMI GALILEO, 2018)
This research examined the effect between beta, firm size, inflation, and interest rate to stock return. This research is based on samples of manufacture, non manufacture firms, and financial firms listed in Indonesia Stock Exchange. Sample is selected based on completely data about dividends, stock price, total debt, total asset, and positive net income. The results of this research indicate that inflation, and interest rate significant impact on stock return. Whereas other variables like beta and firm size are not significant in this model.